Laser-assisted ionization of atomic hydrogen by electrons in the second Born approximation - Zheng, Ming-Yang; Li, Shu-Min (Physical review. A, Atomic, molecular, and optical physics, 2010)
Electron-impact ionization of atomic hydrogen in the presence of a linearly polarized laser field is studied in the second Born approximation. The state of fast electron in the laser field is described by the Volkov state, while the dressed state of the ejected slow electron and atomic hydrogen is treated perturbatively to the first order. We calculate the triple differential cross section in the Ehrhardt asymmetric coplanar geometry. Numerical results show that the triple differential cross sections of the first Born approximation are significantly improved when the second-order corrections are taken into account.
Gesehen am 12.03.2024